Crustal structure of Narmada-Son Lineament: An aeromagnetic perspective - Anand, S.P.; Rajaram, M. (My University, 2004)
Aeromagnetic data analysis over the Narmada-Son Lineament (NSL) shows that prominent anomalies are located over dyke swarms and trap flows and the major formations present have distinct magnetic signatures. A major extensive ENE fault is identified which coincides with the course of the Narmada river and which appears, as earlier suggested, to control Gondwana sedimentation to the south and Vindhyan sedimentation to the north. By isolating the sources, it is found that the signatures of the Deccan traps have a distribution that is possibly related to their time of eruption and subsequent evolution. The region between Hoshangabad (HBD) and Narsimapura (NSR) are made up of two structural units: a shallow ENE structure superposed on a deeper NW-SE feature which is possibly related to the continuation of the Godavari Gondwana Graben towards the northwest. The region north and south of the deep-seated fault F1 has undergone different evolutionary history. The thickness of the magnetic crust in the Narmada-Son region lies between 25 to 31 km, implying a lithological change below this depth. This is borne out by the high velocity layer (7.2 km/s) within the lower crust identified by DSS studies.
Keywords: Magnetic anomalies; Transformations; Rifting; Continental crust; Aeromagnetic perspective; Narmada-Son Lineament (NSL)